Determination of Physical Activity Levels of Karabük University Students - Serkan Revan; Mert Aydogmus; Yılmaz Yüksel; Numan Kayışoğlu (Türk Spor ve Egzersiz Dergisi)
The sedentary lifestyle is one of the most important problems for today's societies. Health-related behaviors that an individual gains early in his life affect the individual's quality of life in adulthood. The purpose of this study was to examine the physical activity (PA) levels of students studying at Karabük University according to the variables of gender, the program attended and body mass index (BMI). A total of 1717 students, 843 males and 874 females, studying in different departments, participated in the study. International Physical Activity Questionnaire (IPAQ) short form was used to collect data in the study. Frequency, percentage, Mann Whitney U, Kruskal-Wallis and chi-square tests were used to analyze the data. As a result of the research, it was seen that 27.8% of the students were not physically active, 38.2% of them had moderate physical activity levels, and 34% had sufficient PA levels. While 45.9% of male students had sufficient PA level, this rate was 22.4% for female students. A significant difference was found in PA scores of the students in terms of gender. A significant difference was found in the scores of vigorous PA according to the BMI of the students. As a result, it was observed that the student's physical activity level was low, the physical activity level changed according to gender, and male students were more active than females. It can be said that BMI is effective on the level of Vigorous Physical Activity.